Trend Analysis of Cutaneous Leishmaniasis Incidence in Izeh County During 2014-2019 - Marziyeh Ahmadi Mirqhaed; Maryam Dastoorpoor; Abdolamir Behbahani (Disease and Diagnosis, 2021)
Background: A cutaneous form of leishmaniasis (cutaneous leishmaniasis, CL) is becoming increasingly common, and this study was conducted to investigate the epidemiological features of CL in the county of Izeh in Khuzestan province. Materials and Methods: This retrospective cross-sectional research was performed during 2014- 2019. Basic demographic and clinical information was gathered from patients with CL referring to Izeh health centre and then processed using SPSS software, version 25.0. Results: Overall, data related to 131 patients were recorded from 2014 to 2019. The incidence of CL showed a decrease from 16.207 to 5.028 per 100000 individuals in Izeh. Based on the analysis of CL incidence in Izeh county, a statistically significant difference was observed through the mentioned six-year study (P<0.05). Male patients with a frequency rate of 65.6% demonstrated a statistically significant association in the CL and the type of gender compared to 34.4% of females (P<0.05). The age group of 20-29 years old (32.1%) had a higher frequency of CL in the age groups. Finally, there was a statistically considerable discrepancy in the frequencies of infected people with CL related to age groups (P<0.05). Conclusion: Based on the findings and other epidemiological characteristics, Izeh does not seem to be an endemic focus of CL. Nonetheless, it is a concerning situation, and proper preparation is strongly advised for disease control and prevention.